The Influence of Financial Literacy and Risk Tolerance on Student Investment Decisions with Demographic Factors as Moderating Variables - Anindya, Camelia Nur; Hasnawati, Sri (International Journal Of Education, Social Studies, And Management (IJESSM), 2024)
This research explores how Financial Literacy and Risk Tolerance affect Investment Decisions, with a particular focus on the role of demographic factors such as Gender and Income as moderating variables. In this study, Financial Literacy and Risk Tolerance are examined as independent variables, while Investment Decision is the dependent variable. The sample for this study comprises 120 respondents, all of whom are students with experience in stock investments. These respondents were selected using a convenience sampling method. The analysis of the data reveals that both Financial Literacy and Risk Tolerance have a significant impact on Investment Decisions made by students. However, the study finds that demographic factors such as Gender and Income do not act as moderators in the relationship between Financial Literacy and Investment Decisions. Similarly, these demographic factors do not moderate the effect of Risk Tolerance on the students' investment decisions. The purpose of this study is to offer insights that could aid in the development of more targeted and effective financial education programs. By understanding the direct influence of Financial Literacy and Risk Tolerance on investment choices and recognizing the non-moderating role of Gender and Income, the study aims to enhance strategies that promote investment participation among students.